A case of co-parasitism of Sarcoptes scabiei (Linnaeus, 1758) (Sarcoptiformes: Sarcoptidae) and Cheyletiella parasitivorax (Mégnin, 1878) (Trombidiformes: Cheyletidae) in a European rabbit in Guatemala - García-Ochaeta, José Francisco; Jacinavicius, Fernando de Castro; Barros-Battesti, Darci Moraes [UNESP]; Ochoa, Ronald; Bassini-Silva, Ricardo (Taylor & Francis, 2020)
Several mite families are specialized to parasitize only mammals causing severe dermatitis on their skins. Furthermore, few studies highlight co-parasitism between these families and their impact on their hosts. We are reporting a case of co-parasitism between two acariform families, Sarcoptidae and Cheyletidae, specifically the presence of Sarcoptes scabiei and Cheyletiella parasitivorax on a rabbit kept in captivity in Guatemala. Also, this is the first report of C. parasitivorax in Guatemala.
Keywords: case report; Leporidae; Mange mites; Neotropical region; scabies